A novel online coupling of ion selective electrode with the flow injection system for the determination of vitamin B1 (Baghdad Science Journal, 2016)
A simple, fast, selective of a new flow injection analysis method coupled with potentiometric detection was used to determine vitamin B1 in pharmaceutical formulations via the prepared new selective membranes. Two electrodes were constructed for the determination of vitamin B1 based on the ion-pair vitamin B1-phosphotungestic acid (B1-PTA) in a poly (vinyl chloride) supported with a plasticized di-butyl phthalate (DBPH) and di-butyl phosphate (DBP). Applications of these ion selective electrodes for the determination of vitamin B1 in the pharmaceutical preparations for batch and flow injection systems were described. The ion selective membrane exhibited a near-Nernstian slope values 56.88 and 58.53 mV / decade, with the linear dynamic range of vitamin B1 was 5 x 10-5- 1 x 10-2 and 1 x 10-4-1 x 10-2 mol.L-1, in batch and FIA, respectively. The limit of detection was 3.5 x 10-5 and 9.5 x 10-5 mol.L-1, with the percentage linearity 98.85 and 95.22 in batch and FIA, respectively. The suggested ion selective electrode has been utilized perfection in the determination of vitamin B1 in pharmaceutical formulations using batch and flow injection system, respectively.